Tourism investment in the State of Tissemsilt between reality and hopes - Slimane, Nessah; Fatma, Rebhi (International journal of economic perspectives, 2025)
This study aims to highlight the reality of tourism investment in the state of Tissemsilt, considering that the state possesses an immense tourist potentials and capabilities that qualify it to be an outstanding tourist destination. The study concludes that the state of Tissemsilt has a significant tourist potentials and capabilities that qualify it to be an outstanding tourist destination. Despite adopting a comprehensive strategy for developing tourism hubs in the state and implementing tourism investment projects, the efforts are still below the required level. Therefore, the development of tourism in the state of Tissemsilt requires a concerted effort and an implementation of plans and programs according to a well-planned and thoughtful strategy and plan, to achieve sustainable local development.